1996
DOI: 10.2307/3870463
|View full text |Cite
|
Sign up to set email alerts
|

PK12, a Plant Dual-Specificity Protein Kinase of the LAMMER Family, Is Regulated by the Hormone Ethylene

Abstract: The ethylene signal is transduced in plant cells via phosphorylation events. To identify protein kinases whose levels of expression are modulated by the plant hormone ethylene, we utilized a differential reverse transcriptase-polymerase chain reaction approach using mRNA extracted from ethylene-treated and untreated tobacco leaves. An ethylene-induced cDNA clone, PK12, encoding a protein kinase, was isolated. PK12 is a new member of the recently defined LAMMER family of protein kinases, which has been identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 51 publications
1
10
0
1
Order By: Relevance
“…2 Similarly, staining of endogenous CLK1 in PC12 cells found it to be mostly cytoplasmic as well. In agreement with a putative signaling role for the CLK kinases is the finding that ethylene stimulation of tobacco leaves stimulates the activity of the tobacco CLK family member, PK12 (24). These finding strongly suggest the existence of cytoplasmic targets for the CLK family kinases and their participation in intracellular signaling pathways.…”
supporting
confidence: 68%
“…2 Similarly, staining of endogenous CLK1 in PC12 cells found it to be mostly cytoplasmic as well. In agreement with a putative signaling role for the CLK kinases is the finding that ethylene stimulation of tobacco leaves stimulates the activity of the tobacco CLK family member, PK12 (24). These finding strongly suggest the existence of cytoplasmic targets for the CLK family kinases and their participation in intracellular signaling pathways.…”
supporting
confidence: 68%
“…Further molecular confirmation of the kinase activity, using other substrates and performing autophosphorylation assays, is under investigation. There are not many plant protein kinases with both activities described so far, and just a few of them, such as ADK1 from Arabidopsis thaliana (Ali et al, 1994), or PK12 (Sessa et al, 1996) and NtDSK1 (Cho et al, 2001) from tobacco, have been confirmed to have dual specificity in vitro. FsPK1 would be the first dual plant PK induced by ABA.…”
Section: Discussionmentioning
confidence: 99%
“…Dual‐specificity protein kinases are a group of protein kinases which are able to phosphorylate both tyrosine and serine/threonine residues [1]. In plants, characterization of dual‐specificity protein kinases that do not belong to the MAP kinase kinase family is restricted to ADK1 from Arabidopsis [2], PRK1 from petunia [3], and PK12 from tobacco [4]. PRK1 is a predominantly pollen‐expressed receptor‐like kinase which autophosphorylates on serine and tyrosine [3].…”
Section: Introductionmentioning
confidence: 99%
“…PK12 is a member of the LAMMER kinases. PK12 activity is rapidly and transiently increased when plants are treated with ethylene [4]. The PK12 kinase phosphorylates serine/arginine‐rich (SR) splicing factors in vivo to alter their activity and the splicing of target mRNAs [7].…”
Section: Introductionmentioning
confidence: 99%